Imigrantes haitianas na cidade de Manaus: mundos do trabalho informal, redes e sociabilidades (2010-2019) - Corrêa, Maria Celestina Barbosa (2020)
This dissertation is the result of research conducted in the years 2018 and 2019 in the city of Manaus, capital of the state of Amazonas, and aims to show the daily experiences of haitian immigrants inserted in informality. The sidewalk sales trade known as "board sales" was analyzed as a space of sociability, as they are places of daily interactions of immigrant women. The dissertation is constructed in three stages, the first with the highlight being the dialogue on the factors that gave rise to the project and the initial challenges of the research field with Haitian immigrants; second brings a historical view on immigrant women as active social subjects in different migratories contexts and the third visualizes haitian immigrants as social subjects that (re)create in daily migration manauara social relations with other immigrants, nonimmigrants and with institutional elements that contribute to the permanence or decision to migrate again. They are women who subversively occupy the sidewalks with their improvised trays, face the daily challenges of sun, rain, surveillance or personal disputes in the informal work world, but remain steadfast in the purpose of dreaming of better living conditions. The various facets that integrate this Haitian immigrant woman invisible by a tray of socks, fruits, vegetables or bonbons that are shown in this dissertation.